Association of Diabetes and Other Clinical and Sociodemographic Factors With Guideline-concordant Breast Cancer Treatment for Breast Cancer. (February 2020) - Gold, Heather T.; Shao, Huibo; Oratz, Ruth; Yu, Onchee; Hammer, Marilyn; Richardson, Stephen; Boudreau, Denise
Abstract : Background: Women with breast cancer have worse health outcomes with co-occurring type 2 diabetes, possibly due to suboptimal breast cancer treatment. Methods: We created a cohort of women ages 66 to 85 y with stage I to III breast cancer from 1993 to 2012 from an integrated health care delivery system (n=1612) and fee-for-service Medicare beneficiaries (n=98, 915), linked to Surveillance, Epidemiology, and End Results (SEER) data (total n=100, 527). We evaluated associations between type 2 diabetes and other factors with undergoing guideline-concordant cancer treatment. We estimated χ 2 tests for univariate analysis and relative risks (RRs) using multivariable log-binomial models for outcomes of (1) overall guideline-concordant treatment, (2) definitive surgical therapy (mastectomy or lumpectomy with radiation), (3) chemotherapy if indicated, and (4) endocrine therapy. Results: Our cohort included 60% of subjects with stage 1 tumors, one quarter below 70 years old, 23% had diabetes, 35% underwent overall guideline-concordant treatment, 24% chemotherapy, and 83% endocrine therapy. Women with diabetes were less likely to undergo overall guideline-concordant treatment (RR: 0.96; 95% confidence interval: 0.94-0.98), and only slightly less likely to undergo guideline-concordant definitive surgical therapy (RR: 0.99; 95% confidence interval: 0.99-1.00). No differences were found for chemotherapy or endocrine therapy. Other factors significantly associated with a lower risk of guideline-concordant care were cancer stages II to III (vs. I; RR=0.47-0.69, P <0.0001), older age (vs. 66 to 69 y; RR=0.56-0.90, P <0.0001), higher comorbidity burden, and Medicaid dual-eligibility. Conclusions: Diabetes was associated with lower adherence to overall guideline-concordant breast cancer treatment. However, higher stage, older age, higher comorbidity burden, and Medicaid insurance were more strongly associated with lower use of guideline-concordant treatment. Given the heavy burden of breast cancer and diabetes, long-term outcomes analysis should consider guideline-concordant treatment. Impact: Other factors besides diabetes are more strongly associated with guideline-concordant breast cancer treatment. Abstract : Supplemental Digital Content is available in the text.